Peeling-induced interfacial roughness and charging for enhanced triboelectric power generation - Da Woon Jin; Hyun Soo Ahn; Dheeraj Kumar; Joo Hyeong Lee; Min Su Kim; Yushin Eom; Ji Ho Youk; Huidrom Hemojit Singh; Jong Hun Kim; Jong Hoon Jung (Nano Trends)
To date, there have been a lot of efforts to enhance the conversion efficiency of triboelectric nanogenerators (TENGs) via physical and chemical modifications of the polymer surface. Herein, we report that a facile peeling of polymer from a substrate can enhance the triboelectric power output. The peeling of spin-coated polydimethylsiloxane (PDMS) from glass and polytetrafluoroethylene (PTFE) substrates has revealed a considerable increase in interfacial roughness and lateral friction. Surface-sensitive X-ray photoemission spectroscopy and non-contact current measurements have also revealed the transfer of counter-material and interfacial charging. The surface roughness of peeled PDMS is significant for the PTFE substrate, while the surface charge is significant for the glass substrate. The triboelectric output power density for peeled PDMS from the substrate is similar, 10.3 µW/cm2, but significantly larger than that for as-grown PDMS (2.2 µW/cm2). The peeling strength of PDMS significantly increases for glass compared to PTFE after the oxygen plasma treatment of substrates. The triboelectric charge of peeled PDMS from a plasma-treated glass substrate is almost 1.3 times larger than that from a PTFE substrate. This work implies that peeling polymer from a rough substrate with a large adhesion force would be a facile and effective way to increase the triboelectric power output, without any delicate surface treatments.